Exploring the spatialities of technological and user re-scripting: The case of decision support tools in UK agriculture. Issue 89 (February 2018) - Rose, David C.; Morris, Carol; Lobley, Matt; Winter, Michael; Sutherland, William J.; Dicks, Lynn V.
Highlights: Scholarship on decision support tools in agriculture suffers from pro-innovation bias. Decision support tools can be shaped through user interaction. Agricultural society can be shaped by decision support tools. Technologies and society are re-scripted at different scales. Abstract: The use of decision support tools on-farm may help to deliver evidence-based guidance to farmers, helping to improve productivity and prevent environmental degradation. While much research has sought to increase the uptake of decision support tools in practice, largely by identifying desirable characteristics of system design, rather little work has used a spatial lens to investigate how they are actually used. Using Latour's notion of 'the script', this paper looks at the spatialities of technological and user re-scripting associated with the introduction of decision support tools on-farm. Although there is some literature on how technologies may be re-scripted by users, studies concerning decision support tools are more limited. Furthermore, while there are studies about how technology (not decision support tools) re-scripts agricultural societies, these are generally concerned with macro-level impacts (e.g. labour changes), rather than exploring life on individual farms. This paper, therefore, focuses on exploring the spatialities of re-scripting, investigating how tools themselves are co-constituted in various ways by different users in different spaces, but more particularly on how life on the farm may be changed by the introduction of decision tools. A case study of decision support tool use on farms in England and Wales demonstrates the need to explore spaces on individual farms if we wish to understand processes occurring at the interface between tools and farmers. Firstly, situated knowledge held by farmers and advisers leads to resistance, negotiation, and re-scripting of decision support tools, which are perceived to provide the 'view from nowhere'. Secondly, the introduction of decision support tools changes the workflows of farmers, affecting how and when they interact with different spaces of their farm. In signalling the need for more research to theorise the spatialities of re-scripting, we briefly explore how our work can inform policy and the development of decision support tools.